Effect of Bio-CNG Flow Rate on Modified Diesel Engine Run with Dual Fuel - Channappagoudra, Manjunath; Ramesh, K; G, Manavendra (International Journal of Engineering and Technology, 2018)
In the first phase of investigation standard engine (SE) parameters are modified and optimized as Injector opening pressure (IOP) of 230 bar, Injection timing (IT) of 26.deg.bTDC, Compression ratio (CR) of 18, Nozzle hole (NH) of 5 hole and Piston bowl geometry (PBG) of Re-entrant toroidal piston bowl geometry (RTPBG)) when engine is operated with B20 (20% dairy scum biodiesel+80% diesel) fuel blend sole. The modified engine with these optimized parameters has shown improved brake thermal efficiency (BTE) when compared to standard engine operated with B20 (B20-SE), which could be attributed to improved fuel atomization, reduction of fuel droplet size, increased cylinder temperature, enhanced swirl and squish in the modified engine. In second phase of investigation, dual fuel (B20+Bio-CNG) experiments are conducted on modified engine to examine the effect Bio-CNG (enriched biogas/methane) flow rates such as 0.12, 0.24, 0.36, 0.48, 0.60 and 0.72 kg/hr on modified engine performance, exhaust emission and combustion characteristics. Then dual fuel experimental results are compared with neat diesel and B20 fuel operations. The dual fueled engine with all Bio-CNG flow rates has resulted lower performance and combustion characteristics with increased emissions (HC and CO) when compared to single fuel (B20) operated engine. From dual operation, it concludes that 0.48 kg/hr Bio-CNG flow rate has experienced the smooth running and improved performance, emission and combustion characteristics among all other Bio-CNG flow rates, hence 0.48 kg/hr Bio-CNG flow rate is optimized.Â Â